Analisis Penggunaan Think Pair Share dan Berpikir Kreatif dalam Pengembangan Kompetensi Profesional Guru Pendidikan Agama Islam di Kecamatan Leuwiliang - Thoni Anthoni Mukti Prasetyo; Ami Primarni; Riyanto (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the implementation of the Think Pair Share (TPS) strategy and creative thinking skills in the development of professional competence of Islamic Religious Education (PAI) teachers in Leuwiliang District. The research approach used is descriptive qualitative, with data collected through observation, in-depth interviews, and document analysis in nine elementary schools in the region. The results of the study show that the implementation of TPS effectively increases student engagement during the learning process, supports the enhancement of teachers' professional competence, particularly in classroom management, and deepens understanding and mastery of teaching materials.In the context of education, Islam emphasizes the importance of knowledge, as mentioned in QS. Al-Mujadilah: 11: يَرْفَعِ اللَّهُ الَّذِينَ آمَنُوا مِنكُمْ وَالَّذِينَ أُوتُوا الْعِلْمَ دَرَجَاتٍ